Strategi Pengembangan Usaha Peternakan Ayam Ras Petelur Afkir Di Kabupaten Kediri - Kanafi, Rahmat; Daroini, Ahsin; Mulyaningtyas, Ratna Dewi (Manajemen Agribisnis: Jurnal Agribisnis, 2024)
The purpose of this research is to determine the development strategy of rejected laying hens in Kediri Regency by analyzing the factors of Strength, Weakness, Opportunity, and Threat. The method used descriptive qualitative, using primary data and secondary data. Data collection techniques in this study were interviews, and observation. Data analysis used SWOT analysis which is used to determine the best business strategy for the company based on internal and external factors. The results had the internal and external matrix analysis in cell IV, namely Growth and Build, and Stability. In this position, stock breeder can choose to carry out a strategy through horizontal integration or carry out a development strategy or just fixed to the set strategy that has been implemented. The most suitable strategy applied by laying hens breeder in Kediri regency is the SO (Strength-Opportunity) Strategy, which uses all the strengths (Strength) of the breeder to take advantage of opportunities (Opportunity), with strategic steps.